Endoscopic Removal of a Bullet in Rosenmuller Fossa: Case Report - Burks, Joshua D.; Glenn, Chad A.; Conner, Andrew K.; Bonney, Phillip A.; Sanclement, Jose A.; Sughrue, Michael E. (Journal of Neurological Surgery Reports, 2016)
Fractures of the anterior skull base may occur in gunshot victims and can result in traumatic cerebrospinal fluid (CSF) leak. Less commonly, CSF leaks occur days or even weeks after the trauma occurred. Here, we present the case of a 21-year-old man with a delayed-onset, traumatic CSF leak secondary to a missile injury that left a bullet fragment in the Rosenmuller fossa. The patient was treated successfully with endoscopic, endonasal extraction of the bullet, and repair with a nasal septal flap. Foreign bodies lodged in Rosenmuller fossa can be successfully treated with endoscopic skull base surgery.
Keywords: Rosenmuller fossa; skull base; anterior; case report; endoscopic; nasal septal flap; endonasal; pharyngeal recess